DIGITAL MARKETING TRAINING VIA MARKETPLACES AND SOCIAL MEDIA: A COMMUNITY SERVICE PROGRAM TO STRENGTHEN COFFEE SHOP BUSINESSES AROUND MOUNT KELUD - Nur Aini Hidayati; Yessi Rahmawati; Widya Sylviana; Shochrul Rohmatul Ajija; Arivia Fikratuz Zakia (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The contemporary digital age presents numerous opportunities and problems that can be leveraged by all societal strata, including rural areas.  One option is utilising marketplaces as a potential sales channel for advertising business products.  Nevertheless, among the Kelud Coffee Business Group supported by LAZ Al Azhar in Laharpang Hamlet, Puncu Village, Kediri Regency, insufficient knowledge and abilities in leveraging marketplaces persist as an obstacle.  This community service initiative was executed using interactive training techniques and direct mentorship over a three-month period, encompassing instruction in marketplace account establishment, product catalogue administration, promotional tactics via social media, and online transaction methodologies.  Assessment was conducted using pre- and post-tests of participants' digital competencies and the observation of gains in online sales.  The activity's outcomes indicated a 22.15% enhancement in digital knowledge and online marketing competencies post-training.  This action demonstrates that digital marketing training via marketplaces and social media can substantially enhance the digital marketing proficiency of local coffee enterprises.